Sufi narratives of intimacy : Ibn 'Arabī, gender, and sexuality - Shaikh, Sa'diyya (Islamic civilization & Muslim networks., 2012)
Thirteenth-century Sufi poet, mystic, and legal scholar Muhyi al-Din ibn al-'Arabi gave deep and sustained attention to gender as integral to questions of human existence and moral personhood. Reading his works through a critical feminist lens, Sa'diyya Shaikh opens fertile spaces in which new and creative encounters with gender justice in Islam can take place. Grounding her work in Islamic epistemology, Shaikh attends to the ways in which Sufi metaphysics and theology might allow for fundamental shifts in Islamic gender ethics and legal formulations, addressing wide-ranging contemporary challenges including questions of women's rights in marriage and divorce, the politics of veiling, and women's leadership of ritual prayer. Shaikh deftly deconstructs traditional binaries between the spiritual and the political, private conceptions of spiritual development and public notions of social justice, and the realms of inner refinement and those of communal virtue. Drawing on the treasured works of Sufism, Shaikh raises a number of critical questions about the nature of selfhood, subjectivity, spirituality, and society to contribute richly to the prospects of Islamic feminism as well as feminist ethics more broadly."--Provided by publisher.